The Berenstain Bears count their blessings - Berenstain, Stan, 1923-2005 (Berenstain, Stan, 1923-2005. First time books., 1995)
During a frightful thunderstorm, Brother and Sister Bear learn that Mama and Papa's love and protection are better blessings than more Bearbie dolls and video games.